Adenosine deaminase activity as a biochemical marker of inflammatory response in goats infected by caprine arthritis-encephalitis virus - de Souza Rodrigues, Luiz Fernando; Franco Oliveira, Maria Emilia [UNESP]; Maia Teixeira, Pedro Paulo [UNESP]; Mesquita Cavalcante, Italo Jose; Vale, Marcus Raimundo (Elsevier B.V., 2012)
Caprine arthritis-encephalitis virus (CAEV) is a lentivirus that causes a chronic and degenerative arthritis and is associated with important economic losses. Adenosine deaminase (ADA) levels increase in some human infectious diseases, such as tuberculosis and acquired immune deficiency syndrome. Due to the similarity between CAEV and human immunodeficiency virus, we hypothesized that ADA activity in goats with clinical signs of CAEV infection is also altered and could serve as a valuable biochemical marker. Adenosine deaminase was assayed using adenosine (Ado) or 2'-deoxyadenosine (dAdo) as substrates, and ADA activity was calculated using the amount of ammonium produced. No significant difference was detected in the activity of the serum enzyme when assayed with Ado (K-m = 49.19 +/- 5.28 mu mol/L) or dAdo (K-m = 41.28 +/- 4.58 mu mol/L). Caprine serum ADA is a thermo-stable enzyme and can be stored at cool temperatures for at least 30 days with no loss of activity. An increase in ADA activity (approximately 2.6-fold) was found in serum and synovial fluid in CAEV infected animals with clinical signs of arthritis compared with uninfected animals. In serum, the ADA cutoff value for CAEV disease using Ado was >34.9 U/L. Adenosine deaminase activity may be used as an important biochemical marker of the inflammatory response induced by CAEV, and its determination in serum using adenosine as a simple and inexpensive method is sufficient to assess the pathological condition of the animal. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Adenosine deaminase; Caprine arthritis-encephalitis; ADA cutoff for CAEV disease